Impact of clinical preparation steps and use of sex-specific reference for accurate antibiotic monitoring in body fluids - Christian Domes; Lisa Graul; Timea Frosch; Juergen Popp; Stefan Hagel; Mathias W. Pletz; Torsten Frosch (Communications Medicine)
Abstract Background Effective antibiotic therapy in critically ill patients requires precise dosing tailored to individual conditions. However, physiological changes in these patients can complicate drug exposure prediction, leading to treatment failure or toxicity. Therapeutic drug monitoring (TDM) is crucial in optimizing antibiotic therapy, with Raman spectroscopy emerging as a promising method due to its speed and sensitivity. Methods The utility of resonance Raman spectroscopy in analyzing clinical urine samples was investigated, specifically focusing on piperacillin concentrations. Samples subjected to various preparation techniques, including freezing, centrifugation, and filtration, were analyzed using deep UV resonance Raman spectroscopy. Data analysis involved preprocessing and chemometric modeling to assess concentration changes and the influence of sample matrix. Results Sample preparation steps induce concentration changes in piperacillin, with freezing having the highest impact. Chemometric modeling reveals that freezing, filtration, and centrifugation, especially when combined, reduce drug concentration. Furthermore, the choice of urine reference for quantification impacts results, with sex-specific urine pools showing better accuracy compared to mixed pools. Conclusions Resonance Raman spectroscopy effectively quantifies piperacillin concentrations in urine. Freezing, centrifugation, and filtration during sample preparation influence drug concentration. Using sex-specific urine pools as references yields more accurate quantification results. These findings underscore the importance of considering sample processing effects and reference selection in TDM studies, offering insights for optimizing antibiotic dosing in critically ill patients. Further validation on a larger scale is warranted to confirm these observations.